Peran Gereja Dalam Akreditasi Perguruan Tinggi Teologi - Maidiantius Tanyid (Proceeding National Conference of Christian Education and Theology, 2023)
The Christian Church must play a role in various aspects for the advancement of ministry and quality improvement both internally and externally to the church. The command of the Lord Jesus in Matthew 28:20 “Teach them to do everything that I teach you. And know that I am with you always, even to the end of the age.” This command became the basis for the church to achieve quality improvement. Churches and universities are two parts that cannot be separated in carrying out the Great Commission of Jesus Christ. The Church must play a role in supporting Christian Education through the formation of the character of human resources in the church. Higher Education is a theological kitchen thar influences the quality of the church and the church becomes an educational agent whose role is to support the growth of quality tertiary institutions. The church’s role is to prepare a quality generation and support the efforts of universities in running the education system to achieve quality universities that are able to compete in various situations.